Development of an anti corrosion coating using organic resins hybrid system / Ramis Rao Subramanian - Ramis Rao, Subramanian (2016)
The objective of this study is to develop anti-corrosion coating using organic resins hybrid system. The hybrid systems were prepared by blending acrylic polyol resin with epoxy polyol resin in various weight ratios using polyisocyanate resin as hardener. A series of acrylic(A) - epoxy(E) resin blends with the ratio of 10A:90E, 20A:80E, 30A:70E, 40A:60E, 50A:50E, 60A:40E, 70A:30E, 80A:20E and 90A:10E have been prepared and applied on the pre-treated cold rolled mild steel panels. In this investigation, no specific hardener was used to cure epoxy resin. The dry film thickness was maintained within the range 40 m to 80 m. The panels were allowed to cure under ambient air condition for one week prior to testing. The physical, mechanical, thermal, structural, electrochemical and corrosion resistance properties were investigated to obtain the best formulation. From these studies, the hybrid binder system with 90A:10E ratio shows excellent properties. This best performing binder system was chosen for the formulation of paint using various inorganic pigments such as Titanium Dioxide (TiO2), Silitin Z 86, Aktisil AM and Aktisil PF 777. This study will demonstrate interesting correlations between viscosity, dry film thickness, adhesion, impact resistance, accelerated UV weathering, acid resistance studies, DSC, EDAX, EIS, FTIR, SEM and TGA to identify the critical pigment volume concentration (CPVC). These studies conclusively confirm that Paint 3, consisting Aktisil AM as pigment at CPVC 20 % provided the best overall anti-corrosion improvement.